2021
DOI: 10.1007/s00394-021-02648-3
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality indices and gastrointestinal cancer risk: results from the Lifelines study

Abstract: Objective To investigate the long-term association between four dietary quality indices and the risk of gastrointestinal (GI) cancer. Methods Baseline details of the dietary intake of participants, assessed by a single food frequency questionnaire from the prospective Lifelines population-based cohort were translated to diet quality scores using several dietary and dietary-lifestyle indices. Incident cases of GI cancer were then assessed by linkage to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Of the 137 included articles, 31 articles described the original development of 35 plant-based diet quality indices ( Table 1 [ [13] , [14] , [15] , 18 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ] and Table 2 [ 15 , 18 , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , 55 ]), and the remaining 106 articles applied the 35 plant-based diet quality indices in an independent sample to the original development population ( Supplemental Table 2 ). The 137 included articles were published from 2007 to 2022, with most published in 2022 ( n = 39), 2021 ( n = 41), 2020 ( n = 20), and 2019 ( n = 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 137 included articles, 31 articles described the original development of 35 plant-based diet quality indices ( Table 1 [ [13] , [14] , [15] , 18 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ] and Table 2 [ 15 , 18 , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , 55 ]), and the remaining 106 articles applied the 35 plant-based diet quality indices in an independent sample to the original development population ( Supplemental Table 2 ). The 137 included articles were published from 2007 to 2022, with most published in 2022 ( n = 39), 2021 ( n = 41), 2020 ( n = 20), and 2019 ( n = 11).…”
Section: Resultsmentioning
confidence: 99%
“… 0–10 Y, on the basis of epidemiological evidence indicating a positive or inverse association between the plant food and health outcomes, as well as German dietary guidelines Dutch Dietary Guidelines (DDG) Index Moazzen et al. 2022 Netherlands [ 52 ] 1 ) Epidemiological evidence for the impact of food components and dietary habits in the development of diet-related chronic diseases 2 ) DDG 3 ) Netherlands Nutrition Centre surveys FFQ 13 Vegetables, fruits, legumes, whole grain products, unsalted nuts, fish, soft margarine, liquid cooking fats, vegetable oil, tea, red and processed meat, SSBs, and alcohol All food groups have a cutoff score for sufficient consumption. Intake scored as adhering (1) or not adhering (0) to the recommended amount per food group.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking tobacco, excessive consumption of alcohol, unhealthy diet, and inactivity are prime examples of adverse health behaviours that increase one's risk of developing cancer [2]. Concerning diet, studies have found that healthy dietary behaviours exert protective effects against cancer risk and mortality [8,9]. A "healthy diet" has previously been defined as "health-promoting and disease-preventing.…”
Section: Diet Exercise and Cancermentioning
confidence: 99%
“…However, hormone therapy also increases the risk of coronary heart disease and breast cancer (Modena et al, 2005; Rossouw et al, 2002; Zhang et al, 2021). People who consume vegetables, fruits, and legumes have a significantly lower risk of CRC than those on a diet based on red meat (Kromhout et al, 2016; Moazzen et al, 2022). Some studies have shown that the lower incidence of CRC in people who prefer soy products, which is related to the abundance of phytoestrogens in soy (Viggiani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%